An Intelligent Method. For Processing String In 3-D Based On Its Minimum Energy. - Budiarto, Rahmat; Hj. Taib, Abdullah Zawawi; Yusoff, Zaharin; Yamada, Masashi (2002)

(untitled)
The problems associated with geometrical model of string (rope) in computer graphics are preserving topology and detail shape, and a large data volume in its processing. As an example, we consider string figures construction in Cat's Cradle game [3].